2015
DOI: 10.3389/fnsys.2015.00060
|View full text |Cite
|
Sign up to set email alerts
|

Visual system plasticity in mammals: the story of monocular enucleation-induced vision loss

Abstract: The groundbreaking work of Hubel and Wiesel in the 1960’s on ocular dominance plasticity instigated many studies of the visual system of mammals, enriching our understanding of how the development of its structure and function depends on high quality visual input through both eyes. These studies have mainly employed lid suturing, dark rearing and eye patching applied to different species to reduce or impair visual input, and have created extensive knowledge on binocular vision. However, not all aspects and typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 302 publications
(398 reference statements)
3
22
0
2
Order By: Relevance
“…In an attempt to account for this uncertainty, we have presented several potential mechanisms for each of the significant changes observed in the diffusion measures. Our rationale for the mechanisms put forward is supported by behavioral neuroimaging findings (e.g., fMRI, proton density scans) in other forms of visual deprivation [Shimony et al, ; Shu et al, ] and controls, and postmortem results from monocularly enucleated animals [Nys et al, ; Toldi et al, ]. Moreover, given that we are using standardized methods and comparing between groups, we are confident that our findings reflect true differences between participants who have undergone early monocular enucleation and binocularly intact controls.…”
Section: Discussionmentioning
confidence: 53%
“…In an attempt to account for this uncertainty, we have presented several potential mechanisms for each of the significant changes observed in the diffusion measures. Our rationale for the mechanisms put forward is supported by behavioral neuroimaging findings (e.g., fMRI, proton density scans) in other forms of visual deprivation [Shimony et al, ; Shu et al, ] and controls, and postmortem results from monocularly enucleated animals [Nys et al, ; Toldi et al, ]. Moreover, given that we are using standardized methods and comparing between groups, we are confident that our findings reflect true differences between participants who have undergone early monocular enucleation and binocularly intact controls.…”
Section: Discussionmentioning
confidence: 53%
“…Based on data presented here, the mechanisms of synaptic plasticity observed from these studies in mouse V1 may similarly apply to mouse FC (e.g., Gavornik & Bear, ). However, the synaptic features of mouse frontal and visual areas are distinct from the analogous monkey visual and frontal areas, and thus, mechanisms for plasticity likely differ between rodents and primates (e.g., Nys, Scheyltjens, & Arckens, ; Testa‐Silva et al, ; Verhoog et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that an acute intravitreal injection with IL-4 leads to a topographical disruption in the untreated ipsilateral retinotectal axons, suggesting that IL-4 change the balance between binocular inputs to synaptic sites in the SC. Actually, different studies have demonstrated that lesion and/or inflammatory manipulations in one eye change the connectivity of the other eye [12,28].…”
Section: Discussionmentioning
confidence: 99%